Broadband Solar Irradiance and Photometric Illuminance at the Tropical Station in Ileife Nigeria - Okogbue, Emmanuel Chilekwu (2015)
The main objectives of this research were to investigate the diurnal variations of the solar radiation fluxes and the associated solar radiation ratios with a view to characterising the sky conditions over Ile-lfe, Nigeria and establishing models for estimating the radiation fluxes at the station.